A mutation in the FAM36A gene, the human ortholog of COX20, impairs cytochrome c oxidase assembly and is associated with ataxia and muscle hypotonia - Szklarczyk, Radek; Wanschers, Bas F. J.; Nijtmans, Leo G.; Rodenburg, Richard J.; Zschocke, Johannes; Dikow, Nicola; van den Brand, Mariël A. M.; Hendriks-Franssen, Marthe G. M.; Gilissen, Christian; Veltman, Joris A.; Nooteboom, Marco; Koopman, Werner J. H.; et al. (Human molecular genetics, 2013)
The mitochondrial respiratory chain complex IV (cytochrome c oxidase) is a multi-subunit enzyme that transfers electrons from cytochrome c to molecular oxygen, yielding water. Its biogenesis requires concerted expression of mitochondria- and nuclear-encoded subunits and assembly factors. In this report, we describe a homozygous missense mutation in FAM36A from a patient who displays ataxia and muscle hypotonia. The FAM36A gene is a remote, putative ortholog of the fungal complex IV assembly factor COX20. Messenger RNA (mRNA) and protein co-expression analyses support the involvement of FAM36A in complex IV function in mammals. The c.154A>C mutation in the FAM36A gene, a mutation that is absent in sequenced exomes, leads to a reduced activity and lower levels of complex IV and its protein subunits. The FAM36A protein is nearly absent in patient's fibroblasts. Cells affected by the mutation accumulate subassemblies of complex IV that contain COX1 but are almost devoid of COX2 protein. We observe co-purification of FAM36A and COX2 proteins, supporting that the FAM36A defect hampers the early step of complex IV assembly at the incorporation of the COX2 subunit. Lentiviral complementation of patient's fibroblasts with wild-type FAM36A increases the complex IV activity as well as the amount of holocomplex IV and of individual subunits. These results establish the function of the human gene FAM36A/COX20 in complex IV assembly and support a causal role of the gene in complex IV deficiency.